Composite hydrocracking catalyst as well as preparation method and application thereof
By loading different active metals on ZSM-5 and Beta molecular sieves, the composite hydrocracking catalyst is prepared, which solves the problem that the existing technology is difficult to take into account both the opening of aromatic rings and the isomerization of alkanes, and the content of aromatic and normalkanes in the transformer oil is achieved, which is a significant reduction in the content of aromatic and normal alkanes in the transformer oil, meeting the requirements of national standards.
Patent Information
- Application Number
- CN202311060824.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-22
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-08-22
AI Technical Summary
Existing hydrocracking catalysts are difficult to take into account both the aromatic ring opening and the isomer properties of alkanes, resulting in the transformer oil produced inability to meet the national standard requirements.
Using a composite hydrocracking catalyst, the cobalt-molybdenum active metal is supported on the ZSM-5 molecular sieve to enhance the adsorption and bond breaking ability of the alkanes, and the nickel-molybdenum active metal is supported on the Beta molecular sieve to enhance the ring-opening cracking reaction of the aromatic hydrocarbons.
It significantly reduces the aromatic and normal alkane content in the transformer oil, improves the stability and color of the oil product, and can take into account the aromatic ring opening and the isomerization properties of alkanes, meeting the national standard requirements of transformer oil.
Smart Images

Figure BDA0004407796950000091 
Figure BDA0004407796950000101 
Figure BDA0004407796950000102
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrocracking, and in particular relates to a composite hydrocracking catalyst. Background Art
[0002] Transformer oil is a special oil that is stable at high temperatures and has excellent electrical insulation properties. It has two important functions in the transformer, namely, suppressing arcs and dissipating heat generated by the transformer. Among the indicators of high-specification transformer oil, high requirements are placed on the aromatic content and pour point. Although the diesel components produced by conventional hydrocracking technology can meet the requirements in terms of distillation range density, it is often difficult to achieve both aromatics and pour point. The main reason is that conventional hydrocracking catalysts often use a single molecular sieve and active metal component, which makes it difficult to take into account the ring opening of aromatics and the isomerization of paraffins, and the transformer oil produced cannot meet the national standard requirements.
[0003] Therefore, it is of great significance for enterprise transformation and efficiency improvement to develop a hydrocracking catalyst that takes into account both the ring-opening of aromatics and the isomerization ability of paraffins, and simultaneously reduce the content of aromatics and normal alkanes in the transformer oil components produced by hydrocracking, so as to produce qualified transformer oil products.
[0004] CN113969180A discloses a low-pressure hydrogenation dearomatization method for hydrocracked diesel fractions. The invention uses a fixed bed hydrogenation device as a reactor, a nickel reduced catalyst, and hydrogenates the hydrocracked diesel fraction at a hydrogen partial pressure of 1-3 MPa to obtain a low-aromatic product, which can meet the dearomatization requirements of producing No. 5 Class I industrial white oil using hydrocracked diesel fractions. However, even if the hydrocracked diesel is deeply hydrogenated and saturated, the pour point of the refined diesel cannot be greatly changed, and it is difficult to directly produce transformer oil.
[0005] CN107619706A discloses a transformer oil and a preparation method thereof. The transformer oil is prepared by using cycloalkyl and paraffinic vacuum distillate oil as raw materials, undergoing a three-stage high-pressure hydrogenation production process, and adding a combined aromatic additive and an antioxidant. The components are calculated by mass percentage, and the paraffinic base oil fraction accounts for 15% to 25%, the combined aromatic additive accounts for 4 to 7%, the antioxidant accounts for 0.3% ± 0.05%, and the balance is cycloalkyl base oil; the transformer oil provided by the transformer oil has excellent carbon structure and anti-gassing performance, and its low temperature performance and antioxidant performance are higher than those of existing products on the market. However, this method has strict requirements on the composition of the raw oil, a complex process flow, and a high production cost of the transformer oil. Summary of the invention
[0006] In view of the deficiencies of the prior art, the present invention provides a method for preparing a composite hydrocracking catalyst and a method for producing qualified transformer oil products using the same.
[0007] The present invention provides a method for preparing a composite hydrocracking catalyst, comprising the following steps:
[0008] (1) ZSM-5 molecular sieve, alumina and a binder are mixed to obtain a carrier I, nickel and molybdenum are loaded on the carrier I, dried and calcined to obtain a catalyst I, wherein the average pore diameter of the catalyst I is 6.0-12.0 nm;
[0009] (2) Beta molecular sieve, alumina and a binder are mixed to obtain a carrier II, cobalt and molybdenum are loaded on the carrier II, dried and calcined to obtain a catalyst II, wherein the average pore size of the catalyst II is 2.0-4.0 nm;
[0010] (3) Catalyst I and catalyst II are mixed to obtain the composite hydrocracking catalyst.
[0011] It should be understood by those skilled in the art that the average pore diameters of Catalysts I and II are different, and the control of the pore diameter is well known to those skilled in the art. Specifically, on the one hand, it can be controlled by the selection of raw materials, for example, in the present invention, it can be achieved by selecting alumina and molecular sieves with different pore diameters and regulating their contents; on the other hand, the pore diameter can be controlled by reaction conditions during the preparation process, such as controlling the temperature and time of drying and calcination, so as to obtain a catalyst with a target pore diameter.
[0012] Furthermore, the active components in steps (1) and (2) are loaded by an impregnation method, including an equal volume impregnation method, an excess volume impregnation method, and a steam impregnation method, etc. The specific operation method is well known to those skilled in the art.
[0013] Furthermore, in steps (1) and (2), the drying temperature is 60-140°C, and the drying time is 2-12 hours; the roasting temperature is 300-550°C, preferably 400-500°C, and the roasting time is 2-12 hours.
[0014] Furthermore, based on the total weight of catalyst I, alumina accounts for 40.0-60.0wt%, ZSM-5 molecular sieve accounts for 10.0-30.0wt%, nickel as oxide accounts for 2.0-8.0wt%, and molybdenum as oxide accounts for 10.0-25.0wt%.
[0015] Furthermore, based on the total weight of Catalyst II, alumina accounts for 60-80wt%, Beta molecular sieve accounts for 5-20wt%, cobalt as oxide accounts for 2-8wt%, and tungsten as oxide accounts for 8-15wt%.
[0016] Furthermore, the weight ratio of the catalyst I and the catalyst II is 1:0.2-1:4, preferably 1:0.5-1:1.
[0017] Furthermore, the specific surface area of the catalyst I is 100-600m 2 / g, pore volume is 0.12-0.45cm 3 / g, and the acid content is 0.10-0.50mmol / g.
[0018] Furthermore, the specific surface area of the catalyst II is 200-700m 2 / g, pore volume is 0.15-0.50cm 3 / g, and the acid content is 0.05-0.40mmol / g.
[0019] Furthermore, the average pore size of catalyst I is 2.0-8.0 nm higher than that of catalyst II.
[0020] Furthermore, the specific surface area of the composite hydrocracking catalyst is 150.0-650.0m 2 / g, average pore diameter of 2.0-10.0nm, pore volume of 0.13-0.47cm 3 / g, and the acid content is 0.10-0.45mmol / g.
[0021] Furthermore, the obtained hydrocracking catalyst may have a shape of a three-leaf clover, a four-leaf clover, a cylinder, a toothed ball, or the like.
[0022] The technical purpose of the second aspect of the present invention is to provide a hydrocracking catalyst prepared by the above preparation method.
[0023] The hydrocracking catalyst of the present invention loads cobalt and molybdenum active metals on ZSM-5 molecular sieves to increase the adsorption capacity for chain alkanes and strengthen the bond breaking and isomerization reactions of chain alkanes. The nickel and molybdenum active metals are loaded on Beta molecular sieves to strengthen the adsorption capacity for aromatics and enhance the ring-opening cracking reaction of aromatics, thereby significantly reducing the aromatic content in transformer oil.
[0024] The technical purpose of the third aspect of the present invention is to provide the application of the above hydrocracking catalyst, which is used for preparing transformer oil by hydrocracking of oil products.
[0025] Furthermore, the oil product is a raw material such as vacuum wax oil, coking wax oil, etc. The density is 0.88-0.94g / cm 3 , initial distillation point is 220-260℃, dry point is 500-580℃, sulfur content is 0.5wt%-3.0wt%, nitrogen content is 200-2000μg·g -1 .
[0026] Furthermore, the temperature of the hydrocracking reaction is 340-420°C, preferably 360-400°C; the reaction pressure is 6.0-15.0MPa, preferably 8.0-12.0MPa; the volume space velocity of the hydrocracking stage is 0.5-4.0h -1 , preferably 1.0-3.0h -1 .
[0027] The technical purpose of the fourth aspect of the present invention is to provide a method for producing transformer oil, wherein the oil product is sequentially passed through a bed layer loaded with a hydrorefining catalyst and the hydrocracking catalyst to produce transformer oil.
[0028] Furthermore, the reaction pressure of the hydrofining is 6.0-15.0MPa, preferably 8.0-12.0MPa; the reaction temperature is 320-400°C, preferably 340-380°C; the volumetric space velocity of the hydrofining is 0.2-2.0h -1 , preferably 0.5-1.5h -1 .
[0029] Furthermore, the temperature of the hydrocracking reaction is 340-420°C, preferably 360-400°C; the reaction pressure is 6.0-15.0MPa, preferably 8.0-12.0MPa; the volume space velocity of the hydrocracking stage is 0.5-4.0h -1 , preferably 1.0-3.0h -1 .
[0030] The oil product is straight-run diesel, catalytic diesel or a mixture thereof. The density is 0.80-0.92 g / cm 3 The initial distillation point is 180-300°C, the final distillation point is 320-420°C, and when the mixed oil of straight-run diesel and catalytic diesel is used as the raw material, the blending ratio of catalytic diesel is 20.0-50.0wt%.
[0031] Compared with the prior art, the method of the present invention has the following beneficial effects:
[0032] (1) The present invention loads cobalt and molybdenum active metals on ZSM-5 molecular sieves to increase the adsorption capacity for chain alkanes, strengthen the bond breaking and isomerization reaction of chain alkanes, significantly reduce the pour point of transformer oil, and improve the yield of transformer oil. The nickel and molybdenum active metals are loaded on Beta molecular sieves to enhance the adsorption capacity for aromatics, strengthen the ring-opening cracking reaction of aromatics, significantly reduce the aromatic content in transformer oil, and improve its stability and chromaticity. After the two are compounded, the indicators of the aromatic content and pour point of transformer oil can be taken into account, and the partitioning and strengthening of the aromatic ring-opening reaction and the chain alkanes bond-breaking isomerization reaction can be achieved, thereby reducing the aromatic content and pour point in hydrocracking diesel, so that conventional hydrocracking means can directly produce qualified transformer oil products.
[0033] (2) In the present invention, by controlling the pore size difference of two different catalysts, the confined conversion of different sizes and types of analysis in the crude oil is achieved. The pore size of the catalyst containing ZSM-5 molecular sieve is larger than that of the catalyst containing Beta molecular sieve. The catalyst containing ZSM-5 molecular sieve with large pore size has high reactant pressure, low diffusion resistance, and less secondary cracking of paraffins. The catalyst containing Beta molecular sieve with small pore size has low reactant pressure, which will promote the flow of large molecular aromatic reactants into the surface of Beta molecular sieve to undergo ring opening and cracking reactions, which is beneficial to reducing the amount of aromatics and coking.
[0034] (3) The hydrogenation catalyst system prepared by the method of the present invention can realize the selective hydrogenation and directional conversion of polycyclic aromatic hydrocarbons, which not only reduces the hydrogen consumption of the device but also produces good quality transformer oil.
[0035] (4) The catalyst prepared by the method of the present invention has a simple preparation process, good reaction activity and selectivity, and requires a low reaction temperature, which can significantly extend the operation cycle of the device. DETAILED DESCRIPTION
[0036] The following is a further description of a method for preparing a hydrocracking catalyst provided by the present invention in conjunction with examples to compare and embody the effects and advantages of the hydrocracking method of the present invention, but the present invention is not limited thereto.
[0037] The experimental methods in the following examples are all conventional methods in the art unless otherwise specified. The experimental materials used in the following examples are all purchased from conventional biochemical reagent stores unless otherwise specified. The properties of the different aluminas used in the examples and comparative examples are shown in Table 1.
[0038] Table 1 Physical and chemical properties of different aluminas
[0039] project Alumina-1 Alumina-2 Average pore size / nm 12.5nm 6.8nm <![CDATA[Pore volume / mL·g -1 > 0.35 0.30 <![CDATA[Specific surface area / m 2 ·g -1 > 112.0 176.5
[0040] In the present invention, unless otherwise specified, percentages refer to mass fractions.
[0041] In the following examples, the specific surface area and pore volume of the catalyst were determined by N2 adsorption-desorption method, the average pore size was determined by BJH method, and the acid content was determined by NH3-TPD method.
[0042] Example 1
[0043] Preparation of composite hydrocracking catalyst HCK-1
[0044] (1) After mechanically mixing 30%wt ZSM-5 molecular sieve and 40wt% alumina-1, a binder was added and fully rolled to form, and then dried at 100°C for 4 hours to obtain a catalyst carrier; nickel and molybdenum active metals were impregnated by an equal volume impregnation method, wherein the mass fraction of Ni in terms of NiO was 4.5wt%, and the mass fraction of Mo in terms of MoO3 was 25.5wt%. Catalyst I was obtained after drying at 100°C for 4 hours and calcining at 500°C for 10 hours.
[0045] (2) After mechanically mixing 20wt% Beta molecular sieve and 60wt% alumina-2, a binder was added and fully rolled to form, and then dried at 60°C for 6h to obtain a catalyst carrier; the catalyst carrier was impregnated with a solution containing cobalt and molybdenum active metal components, and the cobalt and molybdenum active metals were impregnated by an equal volume impregnation method, wherein the mass fraction of Co in terms of CoO was 5.5wt%, and the mass fraction of Mo in terms of MoO3 was 14.5wt%. After drying at 60°C for 6h and calcining at 450°C for 4h, catalyst II was obtained.
[0046] (3) Finally, catalyst I and catalyst II were mechanically mixed in a weight ratio of 1:4 to obtain the final composite hydrocracking catalyst HCK-1.
[0047] Among the composite hydrocracking catalysts, the average pore size of catalyst I is 10.0 nm, and the average pore size of catalyst II is 3.0 nm. The average pore size of catalyst I is 7.0 nm higher than that of catalyst II. The specific surface area of HCK-1 is 245.4 m 2 / g, average pore diameter of 4.4nm, pore volume of 0.27cm 3 / g, and the acid content is 0.25mmol / g.
[0048] Two reactors connected in series were used, and the hydrofining catalyst and the hydrocracking catalyst prepared by the present invention were sequentially loaded, that is, the first reactor was loaded with the hydrofining catalyst FF-66, and the second reactor was loaded with the HCK-1 hydrocracking catalyst. The raw material oil 1 in Table 1 was used as the raw material, and a 2500h process evaluation experiment was carried out according to the process reaction conditions in Table 3.
[0049] Example 2
[0050] Preparation of Composite Hydrocracking Catalyst HCK-2
[0051] (1) After mechanically mixing 10%wt ZSM-5 molecular sieve and 60wt% alumina-1, a binder was added and fully rolled to form, and then dried at 140°C for 6 hours to obtain a catalyst carrier; nickel and molybdenum active metals were impregnated by an equal volume impregnation method, wherein the mass fraction of Ni in terms of NiO was 8.5wt%, and the mass fraction of Mo in terms of MoO3 was 21.5wt%. Catalyst I was obtained after drying at 100°C for 4 hours and calcining at 550°C for 10 hours.
[0052] (2) After mechanically mixing 5wt% Beta molecular sieve and 80wt% alumina-2, a binder was added and fully rolled to form, and then dried at 100°C for 4h to obtain a catalyst carrier; the catalyst carrier was impregnated with a solution containing cobalt and molybdenum active metal components, and the cobalt and molybdenum active metals were impregnated by an equal volume impregnation method, wherein the mass fraction of Co in terms of CoO was 2.5wt%, and the mass fraction of Mo in terms of MoO3 was 12.5wt%. After drying at 80°C for 4h and calcining at 500°C for 6h, catalyst II was obtained.
[0053] (3) Finally, catalyst I and catalyst II were mechanically mixed in a weight ratio of 1:2 to obtain the final composite hydrocracking catalyst HCK-2.
[0054] Among the composite hydrocracking catalysts, the average pore size of catalyst I is 11.5 nm, and the average pore size of catalyst II is 3.5 nm. The average pore size of catalyst I is 8.0 nm higher than that of catalyst II. The specific surface area of HCK-2 is 238.7 m 2 / g, average pore diameter of 6.2nm, pore volume of 0.37cm 3 / g, and the acid content is 0.15mmol / g.
[0055] Two reactors connected in series were used, and the hydrofining catalyst and the hydrocracking catalyst prepared by the present invention were sequentially loaded, that is, the first reactor was loaded with the hydrofining catalyst FF-66, and the second reactor was loaded with the HCK-2 hydrocracking catalyst. The raw material oil 1 in Table 1 was used as the raw material, and a 2500h process evaluation experiment was carried out according to the process reaction conditions in Table 3.
[0056] Example 3
[0057] Preparation of composite hydrocracking catalyst HCK-3
[0058] (1) After mechanically mixing 20%wt ZSM-5 molecular sieve and 50wt% alumina-1, a binder was added and fully rolled to form, and then dried at 80°C for 8h to obtain a catalyst carrier; nickel and molybdenum active metals were impregnated by an equal volume impregnation method, wherein the mass fraction of Ni in terms of NiO was 4.5wt%, and the mass fraction of Mo in terms of MoO3 was 25.5wt%. Catalyst I was obtained after drying at 100°C for 8h and calcining at 450°C for 10h.
[0059] (2) After mechanically mixing 15wt% Beta molecular sieve and 70wt% alumina-2, a binder was added and fully rolled to form, and then dried at 90°C for 4h to obtain a catalyst carrier; the catalyst carrier was impregnated with a solution containing cobalt and molybdenum active metal components, and the cobalt and molybdenum active metals were impregnated by an equal volume impregnation method, wherein the mass fraction of Co in terms of CoO was 3.5wt%, and the mass fraction of Mo in terms of MoO3 was 11.5wt%. After drying at 80°C for 4h and calcining at 500°C for 4h, catalyst II was obtained.
[0060] (3) Finally, catalyst I and catalyst II were mechanically mixed in a weight ratio of 1:1 to obtain the final composite hydrocracking catalyst HCK-3.
[0061] Among the composite hydrocracking catalysts, the average pore size of catalyst I is 6.0 nm, and the average pore size of catalyst II is 3.0 nm. The average pore size of catalyst I is 3.0 nm higher than that of catalyst II. The specific surface area of HCK-3 is 284.4 m 2 / g, average pore diameter is 4.5nm, pore volume is 0.32cm 3 / g, and the acid content is 0.25mmol / g.
[0062] Two reactors connected in series were used, and the hydrofining catalyst and the hydrocracking catalyst prepared by the present invention were sequentially loaded, that is, the first reactor was loaded with the hydrofining catalyst FF-66, and the second reactor was loaded with the HCK-3 hydrocracking catalyst. The raw material oil 2 in Table 1 was used as the raw material, and a 2500h process evaluation experiment was carried out according to the process reaction conditions in Table 3.
[0063] Example 4
[0064] Preparation of Composite Hydrocracking Catalyst HCK-4
[0065] (1) After mechanically mixing 25%wt ZSM-5 molecular sieve and 55wt% alumina-1, a binder was added and fully rolled to form, and then dried at 100°C for 5h to obtain a catalyst carrier; nickel and molybdenum active metals were impregnated by an equal volume impregnation method, wherein the mass fraction of Ni in terms of NiO was 4.5wt%, and the mass fraction of Mo in terms of MoO3 was 15.5wt%. Catalyst I was obtained after drying at 100°C for 5h and calcining at 500°C for 4h.
[0066] (2) After mechanically mixing 12wt% Beta molecular sieve and 68wt% alumina-2, a binder was added and fully rolled to form, and then dried at 120°C for 4h to obtain a catalyst carrier; the catalyst carrier was impregnated with a solution containing cobalt and molybdenum active metal components, and the cobalt and molybdenum active metals were impregnated by an equal volume impregnation method, wherein the mass fraction of Co in terms of CoO was 4.5wt%, and the mass fraction of Mo in terms of MoO3 was 15.5wt%. After drying at 120°C for 3h and calcining at 450°C for 3h, catalyst II was obtained.
[0067] (3) Finally, catalyst I and catalyst II were mechanically mixed at a weight ratio of 2:1 to obtain the final composite hydrocracking catalyst HCK-4.
[0068] Among the composite hydrocracking catalysts, the average pore size of catalyst I is 4.5 nm, and the average pore size of catalyst II is 2.2 nm. The average pore size of catalyst I is 2.3 nm higher than that of catalyst II. The specific surface area of HCK-4 is 346.0 m 2 / g, average pore diameter is 3.7nm, pore volume is 0.32cm 3 / g, and the acid content is 0.35mmol / g.
[0069] Two reactors connected in series were used, and the hydrofining catalyst and the hydrocracking catalyst prepared by the present invention were sequentially loaded, that is, the first reactor was loaded with the hydrofining catalyst FF-66, and the second reactor was loaded with the HCK-4 hydrocracking catalyst. The raw material oil 2 in Table 1 was used as the raw material, and a 2500h process evaluation experiment was carried out according to the process reaction conditions in Table 3.
[0070] Comparative Example 1
[0071] Preparation of Composite Hydrocracking Catalyst HCK-5
[0072] (1) After mechanically mixing 30%wt ZSM-5 molecular sieve and 50wt% alumina-2, a binder was added and fully rolled to form, and then dried at 100°C for 7h to obtain a catalyst carrier; nickel and molybdenum active metals were impregnated by an equal volume impregnation method, wherein the mass fraction of Ni in terms of NiO was 4.5wt%, and the mass fraction of Mo in terms of MoO3 was 15.5wt%. Catalyst I was obtained after drying at 100°C for 6h and calcining at 350°C for 8h.
[0073] (2) After mechanically mixing 20wt% Beta molecular sieve and 50wt% alumina-2, a binder was added and fully rolled to form, and then dried at 60°C for 4h to obtain a catalyst carrier; the catalyst carrier was impregnated with a solution containing cobalt and molybdenum active metal components, and the cobalt and molybdenum active metals were impregnated by an equal volume impregnation method, wherein the mass fraction of Co in terms of CoO was 5.5wt%, and the mass fraction of Mo in terms of MoO3 was 24.5wt%. After drying at 60°C for 4h and calcining at 350°C for 8h, catalyst II was obtained.
[0074] (3) Finally, catalyst I and catalyst II were mechanically mixed in a weight ratio of 1:4 to obtain the final composite hydrocracking catalyst HCK-5.
[0075] Among the composite hydrocracking catalysts, the average pore size of catalyst I is 4.0 nm, and the average pore size of catalyst II is 3.2 nm. The average pore size of catalyst I differs from that of catalyst II by less than 1 nm. The specific surface area of HCK-5 is 447.0 m 2 / g, average pore diameter of 3.4nm, pore volume of 0.38cm 3 / g, and the acid content is 0.23mmol / g.
[0076] Two reactors connected in series were used, and the hydrofining catalyst and the hydrocracking catalyst prepared by the present invention were sequentially loaded, that is, the first reactor was loaded with the hydrofining catalyst FF-66, and the second reactor was loaded with the HCK-5 hydrocracking catalyst. The raw material oil 1 in Table 1 was used as the raw material, and a 2500h process evaluation experiment was carried out according to the process reaction conditions in Table 3.
[0077] Comparative Example 2
[0078] The hydrotreating reactor was loaded with hydrotreating catalyst FF-66, and the conventional industrial FC-46 hydrocracking catalyst was used instead of the hydrocracking catalyst of the present invention and loaded into the second reactor. The feedstock oil 1 in Table 1 was used as the raw material, and a 2500h process evaluation experiment was carried out according to the process reaction conditions in Table 3.
[0079] Comparative Example 3
[0080] The industrial FF-76 hydrotreating catalyst was loaded into the hydrotreating reactor, and the conventional industrial FC-32 hydrocracking catalyst was loaded into the hydrocracking reactor. The crude oil 2 was used as the raw material, and a 2500h process evaluation experiment was carried out according to the conditions in Table 3.
[0081] The properties of the crude oil are shown in Table 2.
[0082] Table 2
[0083]
[0084]
[0085] The catalyst properties of the hydrotreating catalysts FF-66 and FF-46 and the hydrocracking catalysts FC-46 and FC-32 used in Example 5 and Comparative Example 1 are shown in Table 3.
[0086] Table 3
[0087] Industrial Agents FF-66 FC-46 FC-32 Physical and chemical properties Metal Type Ni-Mo Ni-Mo Ni-W Pore diameter / nm 2~8nm 3~9nm 2~8nm <![CDATA[Pore volume / mL·g -1 > ≥0.28 ≥0.30 ≥0.28 <![CDATA[Specific surface area / m 2 ·g -1 > ≥180 ≥320 ≥300 shape Gear Ball Gear Ball Gear Ball <![CDATA[Loading heap ratio, g / cm 3 > 0.75 0.64 0.72
[0088] Table 3 Evaluation conditions
[0089] Reaction pressure, MPa 10.0 <![CDATA[Volume space velocity of the refining agent, h -1 > 2.0 <![CDATA[Cracking agent space velocity, h -1 > 1.5 Nitrogen content of refined oil, ppm 10 Hydrocracking conversion rate, % 70 Hydrogen to oil ratio at the inlet of hydrotreating reactor 600:1 Hydrogen to oil ratio at the inlet of hydrocracking reactor 800:1 Running time, h 2500
[0090] The experimental results after running are shown in Table 4.
[0091] Table 4 Evaluation results of examples and comparative examples
[0092]
[0093]
[0094] It can be seen from the experimental results of the comparative examples and the embodiments that, under the conditions of processing the same raw oil and controlling the same conversion rate, the hydrocracking catalyst of the present invention has good activity, low hydrogen consumption, low aromatic content and pour point of the transformer oil produced, and is a qualified 0# transformer oil. When the catalyst system under the conditions of Example 1 is used, the polycyclic aromatic hydrocarbon content of the transformer oil produced at 275-365°C is the lowest, which is 0.10%, and the pour point is -12°C.
Claims
1. A method for preparing a composite hydrocracking catalyst, comprising the following steps: (1) ZSM-5 molecular sieve, alumina and a binder are mixed to obtain a carrier I, nickel and molybdenum are loaded on the carrier I, dried and calcined to obtain a catalyst I, wherein the average pore size of the catalyst I is 6.0-12.0 nm; (2) Beta molecular sieve, alumina and a binder are mixed to obtain carrier II, cobalt and molybdenum are loaded on carrier II, dried and calcined to obtain catalyst II, wherein the average pore size of catalyst II is 2.0-4.0 nm; (3) Catalyst I and catalyst II are mixed to obtain the composite hydrocracking catalyst.
2. The preparation method according to claim 1, characterized in that: The active components in steps (1) and (2) are loaded by an impregnation method, including an equal volume impregnation method, an excess volume impregnation method and a steam impregnation method.
3. The preparation method according to claim 1, characterized in that In steps (1) and (2), the drying temperature is 60-140°C and the drying time is 2-12 hours; the roasting temperature is 300-550°C and the roasting time is 2-12 hours.
4. The preparation method according to claim 1, characterized in that: Based on the total weight of catalyst I, alumina accounts for 40.0-60.0wt%, ZSM-5 molecular sieve accounts for 10.0-30.0wt%, nickel accounts for 2.0-8.0wt% in terms of oxide, and molybdenum accounts for 10.0-25.0wt% in terms of oxide.
5. The preparation method according to claim 1, characterized in that: Based on the total weight of Catalyst II, alumina accounts for 60-80wt%, Beta molecular sieve accounts for 5-20wt%, cobalt as oxide accounts for 2-8wt%, and tungsten as oxide accounts for 8-15wt%.
6. The preparation method according to claim 1, characterized in that: The weight ratio of the catalyst I and the catalyst II is 1:0.2-1:
4.
7. The preparation method according to claim 1, characterized in that The average pore size of catalyst I is 2.0-8.0 nm higher than that of catalyst II.
8. The preparation method according to claim 1, characterized in that The specific surface area of the composite hydrocracking catalyst is 150.0-650.0 m 2 / g, average pore diameter of 2.0-9.0 nm, pore volume of 0.13-0.47 cm 3 / g, and the acid content is 0.10-0.45mmol / g.
9. The hydrocracking catalyst prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the hydrocracking catalyst according to claim 9, wherein the hydrocracking catalyst is used for preparing transformer oil by hydrocracking of oil products.
11. The use according to claim 9, characterized in that: The oil product is vacuum wax oil and coker wax oil. The temperature of the hydrocracking reaction is 340-420°C, the reaction pressure is 6.0-15.0MPa, and the volume space velocity of the hydrocracking section is 0.5-4.0h -1 .
12. A method for producing transformer oil, characterized in that: The oil product is sequentially passed through a bed filled with a hydrorefining catalyst and a hydrocracking catalyst as claimed in claim 10 to produce transformer oil.
13. The method according to claim 12, characterized in that The oil product is straight-run diesel, catalytic diesel or a mixture thereof. When the mixture of straight-run diesel and catalytic diesel is used as the raw material, the blending ratio of the catalytic diesel is 20.0-50.0wt%.
Citation Information
Patent Citations
Transformer oil and preparation method thereof
CN107619706A
Low-pressure hydrogenation dearomatization method of hydrocracking diesel oil fraction
CN113969180A
Combined hydrocracking method
CN101003746A
Catalytic cracking method for producing low-carbon olefins and light aromatic hydrocarbons
CN107971012A
Blended diesel hydrocracking method
CN108795489A